(untitled) (Хабаршы. Психология және социология сериясы, 2021)
The covid-19 pandemic has changed the notion of education completely. All kind of educational institutions had to switch to distance learning urgently. Such immediate transmission to new educational format requires suitable approaches and methods to meet the students’ needs. Therefore, numbers of researchers started studying this issue to design an effective Instructional design for e-learning. The cur- rent article is aimed to analyze existing researches in the field of Instructional Design to determine the most common approach to e-learning. To fulfill the goal various theories and model before and during quarantine were collected and reviewed. The study has shown that major part of authors assume that e-learning requires an instant and timely feedback to students. Moreover, it was derived that one of the necessary change differing from traditional face-to-face sessions is breaking down the topic and mate- rial into smaller pieces. That will help student to perceive information more effectively. Some of the researchers suggest the idea that students must have a chance to study at their own pace, which will increase the understanding. Key words: COVID-19, Instructional design, pandemic, e-learning, distance learning, remote learn- ing, online education.